Internal forced displacement and crime: Evidence from Colombia (2018)
Internal forced displacement, a phenomenon associated to internal conflict, poses important socio-economic challenges for the receiving areas. One of the most relevant aspects is related to crime, since the reception of forced displaced persons might increase inequality and the heterogeneity of population. This paper studies the relationship between internal forced displacement and crime. We use a panel of Colombian municipalities for the period 2003-2016. We include spatial patterns for the study of crime, allowing to capture the dynamics of this relationship across time and space. Our results provide evidence of a spatial correlation between crime and internal forced displacement.